Editor's Choice – Occurrence and Classification of Proximal Type I Endoleaks After EndoVascular Aneurysm Sealing Using the Nellix™ Device. (December 2017) - van den Ham, Leo H.; Holden, Andrew; Savlovskis, Janis; Witterbottom, Andrew; Ouriel, Kenneth; Reijnen, Michel M.P.J.; ,
Abstract : Objective/Background: Proximal type I endoleaks are associated with abdominal aortic aneurysm (AAA) growth and rupture and necessitate repair. The Nellix™ EndoVascular Aneurysm Sealing (EVAS) system is a unique approach to AAA repair, where the appearance and treatment of endoleaks is also different. This study aimed to analyse and categorise proximal endoleaks in an EVAS treated cohort. Methods: All patients, treated from February 2013 to December 2015, in 15 experienced EVAS centres, presenting with proximal endoleak were included. Computed tomography scans were analysed by a core laboratory. A consensus meeting was organised to discuss and qualify each case for selection, technical aspects, and possible causes of the endoleak. Endoleaks were classified using a novel classification system for EVAS. Results: During the study period 1851 patients were treated using EVAS at 15 centres and followed for a median of 494 ± 283 days. Among these, 58 cases (3.1%) developed a proximal endoleak (1.5% early and 1.7% late); of these, 84% of 58 patients were treated outside the original and 96% outside the current, refined, instructions for use. Low stent positioning was the most likely cause in 44.6%, a hostile anatomy in 16.1%, and a combination of both in 33.9%. Treatment, by embolisation or proximal extension, was performed in 47% of cases, with a technical success of 97%. Conclusion: The overall incidence of proximal endoleak after EVAS is 3.1% after a mean follow-up period of 16 months, with 1.5% occurring within 30 days. Their occurrence is related to patient selection and stent positioning. Early detection and classification is crucial to avoid the potential of sac rupture.